Lifestyle Behaviors and Physical Activity as Modifiable Determinants of Chronic Disease - Ciupak, Klaudia; Garbacki, Klaudiusz; Dudek, Bartosz; Popek, Lena; Błażukiewicz, Jan; Dudek, Karolina; Kowalczyk, Natalia; Kowalewski, Piotr; Kuchta, Eliza (Quality in Sport, 2026)
Background Cardiovascular diseases remain a major cause of morbidity and mortality worldwide. Their development is strongly associated with modifiable lifestyle factors, including unhealthy diet, physical inactivity, chronic stress, sleep disturbances, and substance use. Aim The aim of this study was to evaluate the association between lifestyle factors and the risk of cardiovascular disease. Materials and Methods This narrative review analyzed 31 peer-reviewed publications, including cohort studies, randomized clinical trials, systematic reviews, and international guidelines related to chronic disease prevention and cardiometabolic health. The review focused on diet, physical activity, sleep, stress, substance use, and their effects on metabolic and inflammatory pathways. Results Healthy lifestyle behaviors, particularly plant-based dietary patterns, were associated with lower cardiovascular risk, with studies reporting an approximate 14% reduction. Benefits included improved lipid profile, lower inflammation, and better metabolic regulation. Regular physical activity, adequate sleep, and stress reduction further enhanced these effects. Emerging evidence suggests that metabolic biomarkers may better reflect lifestyle-related disease risk than traditional self-reported methods. Conclusions Lifestyle plays a central role in cardiovascular disease prevention. Its individual components interact through shared metabolic, inflammatory, and vascular mechanisms. Even partial improvement in health behaviors may provide measurable clinical benefits, supporting the importance of comprehensive lifestyle-based prevention strategies.